2015
DOI: 10.1002/2015sw001201
|View full text |Cite
|
Sign up to set email alerts
|

Precise point positioning performance in the presence of the 28 October 2003 sudden increase in total electron content

Abstract: Intense disturbances in the ionosphere may produce perturbations in Global Navigation Satellite Systems (GNSS) radio signals that in the most severe cases produce receiver tracking problems, which in turn impact on GNSS positioning accuracy. In this paper we present a case study related to the sudden increase in total electron content (SITEC) induced by the X17.2 solar flare that occurred on 28 October 2003. This is the largest SITEC ever recorded by means of the rate of change of total electron content. A sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
1
22
0
2
Order By: Relevance
“…Reconnection is the key driver of many important aspects of space weather both on the solar side and on Earth's side. In the solar corona (the Sun's hot and tenuous atmosphere), reconnection enables solar flares and coronal mass ejections (CMEs) [Priest and Forbes, 2002], the most energetic events in the solar system; indeed, it is in this context that reconnection was discovered in the 1940s. Shown in Figure 2a is a schematic diagram capturing the role of reconnection for a particular type of flare.…”
Section: Magnetic Reconnection and Space Weathermentioning
confidence: 99%
“…Reconnection is the key driver of many important aspects of space weather both on the solar side and on Earth's side. In the solar corona (the Sun's hot and tenuous atmosphere), reconnection enables solar flares and coronal mass ejections (CMEs) [Priest and Forbes, 2002], the most energetic events in the solar system; indeed, it is in this context that reconnection was discovered in the 1940s. Shown in Figure 2a is a schematic diagram capturing the role of reconnection for a particular type of flare.…”
Section: Magnetic Reconnection and Space Weathermentioning
confidence: 99%
“…The GEM Challenge study revealed that adding the Hall term into resistive MHD gives reconnection rates comparable to those of kinetic simulations, while not including it leads to resistive reconnection. One explanation for this is that the Hall term leads to faster fl ows at small scales (it is dispersive), which leads to an open exhaust and therefore faster reconnection [Rogers et al, 2001], though this interpretation remains controversial [Liu et al, 2014]. Thus, while not being the effect that breaks fi eld lines, the Hall effect can be very important.…”
Section: Fluid Description Of the Diffusion Regionmentioning
confidence: 99%
“…In the solar corona (the Sun's hot and tenuous atmosphere), reconnection enables solar fl ares and coronal mass ejections (CMEs) [Priest and Forbes, 2002], the most energetic events in the solar system; indeed, it is in this context that reconnection was discovered in the 1940s. Shown in Figure 2a is a schematic diagram capturing the role of reconnection for a particular type of fl are.…”
Section: Magnetic Reconnection and Space Weathermentioning
confidence: 99%
See 2 more Smart Citations